Relationship between endothelial progenitor cells and vascular endothelial growth factor and its variation with exercise. (January 2016) - Gagliardi, Juan A.; Maciel, Neiva; Castellano, José L.; Masoli, Osvaldo; Miksztowicz, Verónica; Berg, Gabriela; Bermejo, Emilse; Lazzari, María; Gelpi, Ricardo J.
Abstract: Background: The aim of our study was to evaluate the effect of programmed physical activity and a single exercise test on the number of CD309 + circulating endothelial progenitor cell (EPC) and their relation to the variation in plasma levels of VEGF in chronic coronary patients. Methods: 21 patients < 75 years with chronic stable coronary artery disease were included. All patients underwent exercise myocardial perfusion SPECT. Then, participants were divided into two groups: one group (11 patients) underwent cardiac rehabilitation program and the other (10 patients) continued with the standard treatment. Blood samples were obtained at baseline, 30 min after exercise ended and at one and three months during follow-up. Results: VEGF values decreased significantly after exercise SPECT test. After one month, there was a significant increase in VEGF levels compared to those measured immediately after exercise. All patients showed a decrease in the values of EPC at 1 and 3-month follow-up. There was an inverse and statistically significant relation between change of EPC and VEGF between the baseline and 1 month. Conclusions: The increase of VEGF at 1-month, with respect to baseline values correlated with decreased levels of EPC. This association was independent of the onset of ischemia in the perfusion study. Highlights: VEGF values decrease after acute exercise and significantly increase after 1 month. CD309 endothelial cells decrease after 1 and 3 months independently of exercise. An inverse relation between change of EPC and VEGF at 1 month was observed. These associations were independent of the presence of ischemia or type of exercise.